Decriminalization of abortion – A human rights imperative. (January 2020) - Erdman, Joanna N.; Cook, Rebecca J.
Abstract: This chapter reviews the evolving consensus in international human rights law, first supporting the liberalization of criminal abortion laws to improve access to care and now supporting their repeal or decriminalization as a human rights imperative to protect the health, equality, and dignity of people. This consensus is based on human rights standards or the authoritative interpretations of U.N. and regional human rights treaties in general comments and recommendations, individual communications and inquiry reports of treaty monitoring bodies, and in the thematic reports of special rapporteurs and working groups of the U.N. and regional human rights systems. This chapter explores the reach and influence of human rights standards, especially how high courts in many countries reference these standards to hold governments accountable for the reform and repeal of criminal abortion laws. Highlights: Human rights require the withdrawal of punitive abortion measures. Human rights require access to abortion atleast on grounds of life health, sexual crime, and fetal impairment. Human rights require timely access to information of the pregnancy and grounds for its possible termination, written reasons for denials, and review mechanisms for denials. Human rights require that abortion services be available to all, irrespective of their specific circumstance. Decriminalization of abortion is the removal of abortion from the criminal law.